Determining the Gibbs Energy Contributions of Ion and Electron Transfer for Proton Insertion in ϵ‐MnO2. Issue 24 (17th October 2022) - Malaie, Keyvan; Scholz, Fritz; Schröder, Uwe; Wulff, Harm; Kahlert, Heike
Abstract: Electrochemically active ϵ‐MnO2 and ɣ‐MnO2 as tunnel‐type host‐guest structures have been extensively studied by crystallography and electrochemical techniques for application in battery cathode materials. However, the Gibbs energies of the underlying ion and electron transfer processes across the electrode interfaces have not yet been determined. Here we report for the first time these data for ϵ‐MnO2 . This was possible by measuring the mid‐peak potentials in cyclic voltammetry and the open‐circuit potentials under electrochemically reversible conditions. Abstract : The Gibbs energy contributions of ion‐ and electron‐transfer steps for the proton‐insertion battery cathode ϵ‐MnO2 were determined for the first time based on its reversible voltammetry and open‐circuit potentiometry responses, and they were used to discuss its performance.